Nano-sized Fe-Metal Catalyst on TiO2-SiO2: (Photo-assisted Deposition and Impregnation) Synthesis Routes and Nanostructure Characterization - Mohamed, R.M.; S. Aazam, Elham (Asian Journal of Chemistry, 2013)
The photo-assisted deposition and impregnation synthesis of nano-sized Fe metal on TiO2-SiO2 are reported. The prepared catalysts were characterized by different techniques such as XRD, XAFS, TEM and nitrogen adsorption analysis. Photocatalytic reactivity using Fe-TiO2-SiO2 catalysts under visible-light condition on the reduction of Hg2+ to Hg0 was evaluated. The results have shown notable photocatalytic activity of photo-assisted deposition of Fe/TiO2-SiO2 which was 2 and 10 times higher than that of impregnation synthesis of Fe/TiO2-SiO2 and TiO2-SiO2, respectively.